Incorporating One Health competencies into the medical curriculum: Need of the hour - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Indian Journal of Health Sciences and Biomedical Research KLEU, 2022)
The manner in which a doctor approach patient care significantly depends on the way in which they were trained during their undergraduation period. The purpose of the current review is to explore the necessity to incorporate One Health competencies in the medical curriculum and devise a framework for the same. An extensive search of all materials related to the topic was carried out on the PubMed search engine and a total of 14 articles were selected based on their suitability with the current review objectives. Keywords used in the search include One Health and medical education in the title alone only. The analysis of the major outbreaks of infectious diseases in the last couple of decades has shown an association with environmental changes. The presence of all these factors has compelled the international welfare agencies and public health authorities to adopt a One Health approach in medical curriculum to integrate humans, animals, and the ecosystem for the containment of these infectious diseases. To ensure that the current crop of medical students who will be joining the health workforce on completion of their training should be trained in different aspects of one health during their undergraduation period. In conclusion, the training of medical students on the One Health approach is an essential aspect of medical training considering the trends of outbreaks of infectious disease outbreaks. It is high time to acknowledge the need and prepare medical students to work as effective members of the interprofessional team and accordingly incorporate One Health competencies into the medical curriculum.